Investigating Countermovement and Horizontal Jump Asymmetry in Female Football Players: Differences Across Age Categories - Elena Mainer-Pardos; Rafael Albalad-Aiguabella; Víctor Emilio Villavicencio Álvarez; Santiago Calero-Morales; Demetrio Lozano; Alberto Roso-Moliner (Journal of Functional Morphology and Kinesiology)
Background: Lower limb asymmetry is a critical factor influencing performance and injury risk in football players. Despite the increasing popularity of women’s football, limited research has examined how asymmetry varies across different age categories. This study aimed to investigate countermovement jump (CMJ) and horizontal jump (HJ) asymmetry in female football players across four age categories (U14, U16, U18, and +18). Methods: Seventy-six female football players from the same club participated in the study. Players performed unilateral CMJ and HJ tests to assess inter-limb asymmetry. A one-way ANOVA and Chi-square tests were conducted to examine age-related differences in asymmetry levels. Results: CMJ asymmetry significantly varied across age groups (p < 0.001), with the highest asymmetry observed in U14 and the lowest in +18. In contrast, HJ asymmetry remained consistently low across all age groups (p = 0.113). No significant correlation was found between CMJ and HJ asymmetry. Additionally, asymmetry levels in CMJ were significantly associated with age (p = 0.003), whereas no such association was observed for HJ. Conclusions: CMJ asymmetry is more prevalent in younger female football players and tends to decrease with age, suggesting that neuromuscular development plays a role in reducing asymmetry over time. These findings highlight the importance of monitoring asymmetry levels across different age groups to optimize training interventions and injury prevention strategies.